PREPARATION AND EVALUATION OF ANTIDIABETIC LOZENGES FROM GYMNEMA SYLVESTRE - Thorat Priyanka Fulchand; Thorat Akash Fulchand (International Journal of Pharmacy and Analytical Research, 2025)
Gymnema sylvestre has the ability to lower glucose levels without causing hypoglycemia. The leaves of G. sylvestre are widely used in Indian proprietary medicines for the treatment of diabetes and as a diuretic, and in most of the country's herbal drug markets, the leaves are sold alongside the plant's aerial parts under the name Gurmarbuti. The leaves of G. sylvestre contain oleanane- and dammarene-class triterpene saponins. Oleanane saponins consist of gymnemic acids and gymnemasaponins, whereas dammarene saponins consist of gymnemasides. The leaves of G. sylvestre have been found to induce hypoglycemia in laboratory animals and to be useful in herbal medicine for the treatment of diabetes in adults. Gymnema leaf extract has laxative, diuretic, and cough suppressant properties. Gymnema may be useful in both adult-onset (NIDDM) and juvenile-onset (IDDM) diabetes mellitus to facilitate insulin entry into cells.